Liquid plasticine: controlled deformation and recovery of droplets with interfacial nanoparticle jamming. Issue 6 (8th January 2016) - Li, Xiaoguang; Xue, Yahui; Lv, Pengyu; Lin, Hao; Du, Feng; Hu, Yueyun; Shen, Jun; Duan, Huiling
Abstract : An effective control of the shape and transparency of a water droplet is realized based on interfacial jamming of nanoparticles. Abstract : Air-exposed droplet systems are widely applied in material preparation and experimental design. Recently, a droplet system with unusual properties featured by a liquid-like appearance and solid-like deformability was produced. However, it was then just an interesting and perplexing phenomenon in the absence of basic understandings and clear perspectives for applications. Here we reveal that stable droplet deformation is attributed to monolayer nanoparticle jamming at the water/vapor interface, and that the normal shape can be recovered by jamming relieving. The degree of jamming affects the droplet shape and transparency and can be tuned by the squeezing force and droplet volume. Using these properties and control methods, we develop the deformed droplet into "liquid plasticine" with predesigned shapes, super-high transparency, and arbitrarily large volume. We demonstrate that liquid plasticine could be used as liquid lenses, channel-like containers, and miniature reactors.